A Comparative Study of English Language Teaching Methodologies in Uzbekistan and South Korea - Muxlisa, Xoltoʻrayeva (Journal of Innovation in Education and Social Research, 2026)
This study presents a comparative analysis of English Language Teaching (ELT) methodologies employed in Uzbekistan and South Korea, two countries that recognize English as a critical tool for global communication, academic advancement, and economic development. The purpose of the research is to identify similarities and differences in pedagogical approaches, classroom practices, and instructional priorities within the distinct socio-educational contexts of the two nations. The study adopts a qualitative comparative research design based on systematic document analysis of national curricula, educational policy documents, teacher training frameworks, and recent peer-reviewed academic literature. The comparative analysis highlights that effective ELT is shaped not only by methodological choices but also by assessment systems, cultural expectations, and policy consistency. The study suggests that Uzbekistan may benefit from adapting South Korea’s technology integration and teacher training models, while South Korea could reconsider assessment-driven instruction to reduce learner anxiety and promote meaningful communication. The results contribute to the field of applied linguistics and comparative education by providing context-sensitive insights into ELT methodology development and offering practical implications for policymakers, educators, and curriculum designers.